Deficits in oral health behavior and oral health status in patients after lung transplantation. (9th December 2016) - Marcinkowski, Anna; Ziebolz, Dirk; Kleibrink, Bjoern E.; Weinreich, Gerhard; Kamler, Markus; Teschler, Helmut; Sommerwerck, Urte
Abstract: Background: Dental status has been implicated in several systemic inflammatory diseases and is a potential focus for systemic infections. Therefore, most lung‐transplant centers have recommendations regarding pre‐transplant dental care and follow‐up, but there are no official clinical guidelines. To date there is little information on oral health status in lung transplant (LTx) recipients. The aim of this study was to systematically assess oral health status in LTx recipients. Objectives: The aim of this study was to assess oral health status, including periodontal disease, oral health behavior, and awareness of the need for good oral health after LTx. Methods: LTx recipients were recruited during follow‐up outpatient visits at a university clinic transplant unit. Oral health status was quantified using the count of Decayed, Missing, and Filled Teeth (DMF‐T) and the grade of periodontal disease was measured by probing depth. Patients' oral health behavior was assessed using a questionnaire. Results: Seventy‐three patients were included at 5.8 ± 3.4 years after lung transplantation. The mean DMF‐T was 21.9 ± 5.5. Patients with cystic fibrosis as the indication for transplantation had a significantly lower DMF‐T than patients with chronic obstructive pulmonary disease as the transplant indication. Of the 66 patients with teeth, 97% had moderate or severe periodontal disease. The prevalence of moderate or severe periodontal disease was significantly higher in LTx recipients (mean age 55.9 years) compared with older individuals (age 65‐74 years) from the German general population ( P < .005). Conclusions: This single center study shows deficits in oral health and oral health behavior in patients after LTx. There is a strong need for interdisciplinary collaboration and clinical guidelines to foster better oral health education of the transplant recipient and better oral health.